Respuesta :

Answer:

(1, 1 )

Step-by-step explanation:

Given the 2 equations

2x - 4y = - 2 → (1)

3x + y = 4 → (2)

Multiplying (2) by 4 and adding the result to (1) will eliminate the y- term

12x + 4y = 16 → (3)

Add (1) and (3) term by term to eliminate y

14x + 0 = 14

14x = 14 ( divide both sides by 14 )

x = 1

Substitute x = 1 into either of the 2 equations and solve for y

Substituting into (2)

3(1) + y = 4

3 + y = 4 ( subtract 3 from both sides )

y = 1

solution is (1, 1 )

ACCESS MORE